Analisis Makna Motivasi Dalam Lirik Lagu “Dreamers” Karya Jungkook dan Fahad Al Kubaisi - Zenith Betanissa (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Communication from time to time continues to experience development, starting from the use of smoke signals, drums, the invention of paper, the telegraph, telephone, computer, e-mail to a song. Teenagers in Indonesia today are very fond of watching and following boy bands from Korea. One of them is the character Jungkook. Especially now that the 2022 FIFA World Cup is being held which invites one of the Korean boy band personnel, Jungkook who sings with Fahad Al Kubaisi where he sings a song called "Dreamers". This song became widely discussed on social media and attracted people to follow it. This research is intended to find out the meaning contained in the lyrics of the song and examine how the signifier and the signified are. The semiotic theory used to analyze the lyrics of the song "Dreamers" is the theory of Ferdinand De Saussure. The method in this study uses qualitative methods. The result of this study is that it was found that the lyrics of the song "Dreamers" contain the meaning of a motivational message. In addition, this research is able to provide another meaning of parable which is described through Ferdinand De Saussure's theory of semiotic analysis.